2022
DOI: 10.1111/nin.12516
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students doing gender: Implications for higher education and the nursing profession

Abstract: The average age of women nursing students in Australia is rising. With this comes the likelihood that more now begin university with family responsibilities, and with their lives structured by the roles of mother and partner. Women with more traditionally gendered ideas of these roles, such as nurturing others and selfsacrifice, are known to be attracted to nursing as a profession; once at university, however, these students can be vulnerable to gender role stress from the competing demands of study. A qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…This study also showed that age and gender were not related to the implementation of nursing care. Age in this study does not form a construct of nursing factors because the knowledge, competence and skills of nurses or the performance of nurses in providing nursing care are not only influenced by the age and gender of a nurse but by various other influencing factors such as skills, length of work, and training (Andrew et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that age and gender were not related to the implementation of nursing care. Age in this study does not form a construct of nursing factors because the knowledge, competence and skills of nurses or the performance of nurses in providing nursing care are not only influenced by the age and gender of a nurse but by various other influencing factors such as skills, length of work, and training (Andrew et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study in Australia showed that nursing students with less traditional gender beliefs are more autonomous and re ect more on care interventions. Integration of gender theory is therefore considered necessary to empower female nursing students, make them aware of sociocultural gender roles and how to overcome them and thus improve their professional competence (Andrew et al, 2023). Verdonk et al (2018) developed the Nijmegen Gender Awareness Scale that was used in several countries for medical students, e.g., in Portugal (Morais et al, 2020), Sweden (Andersson et al, 2012), Switzerland (Rrustemi et al, 2020) as well as in Italy (Bert et al, 2022) and was also applied for nursing science (Aliri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the working environment of nurses is still based on traditional gender roles with the female nurse being expected to serve. This can be a barrier for the development of critical thinking and gender aware teaching and learning in nursing education and thus sex and gender aware nursing care Although knowledge of sex and gender differences is discussed more frequently in nursing training than in medical school, this is left to chance and not systematically implemented (Andrew et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The background of nursing shows that the profession’s image has always been determined by the public perspectives, whereby these perspectives have the power to affect the users of health services, the nurses’ performance, health policy, and even the choice to become a nurse [ 9 ]. Therefore, the changing trend of gender diversity of nurses triggers public perspective about the impact of diversity in nursing care, collaboration aspects, image of the profession, retention of male nurses, and preferences of nursing gender by patients [ 10 ]. Even though some studies have been previously conducted to discover the public perspective on nursing gender [ 11 , 12 ], there are still conflicting results as some reported positive perspectives and other negative perspectives and most of the studies targeted nursing students and patients while abandoned licensed nurses and non-healthcare providers.…”
Section: Introductionmentioning
confidence: 99%